Hubungan Karakteristik dan Lingkungan Belajar Klinik dengan Kecemasan Mahasiswa Saat Praktek Klinik di Rsjd Dr Amino Gondohutomo Semarang - Dwi Indah Iswanti; Kanthi Suratih; Wenni Winasti (Universitas Muhammadiyah Semarang, 2015)
Nursing students often experience anxiety during studying nursing including currentclinical practice. Students experience new situations and circumstances in the hospital environment, but itis a source of anxiety is when the students are required to provide nursing actions to patients (Helena2003, dalam Anggelina 2012). Purpose: The purpose of this study was to determine the correlation ofstudent characteristics and clinical learning environment toward the current anxiety clinical practice inDr. Amino Gondohutomo RSJ Semarang. Methods: This research method is a kind of analytical researchwith correlational cross-sectional approach. The number of respondents in this study was 92 people withproportional stratified random sampling. And the analysis technique Chi Square test. Results: The resultsof the chi square test between age and anxiety level obtained chi square value of 18.411 (p = 0.000<0.05), chi square test results between the sexes with anxiety levels obtained chi square value of 12.151(p = 0.002 <0.05) , chi square test results between education and anxiety levels obtained chi square valueof 15.866 (p = 0.000 <0.05), chi square test results between clinical learning environment with a level ofanxiety obtained chi square value of 54.672 (p = 0.000 <0, 05). Conclusion: There was a relationshipbetween age, sexes, the level of education at the time of the students' anxiety, and there was a correlationbetween the clinical learning environment on students' anxiety in clinical practice in Dr. RSJD. AminoGondohutomo Semarang